Cell‐free fetal DNA in maternal circulation after chorionic villous sampling. (31st May 2013) - Di Tommaso, Mariarosaria; Seravalli, Viola; Salvianti, Francesca; Bussani, Cecilia; Pasquini, Lucia; Cordisco, Adalgisa; Pinzani, Pamela; Chitty, Lyn S.; Bianchi, Diana W.
ABSTRACT Objective This study aims to estimate whether chorionic villous sampling (CVS) causes a significant increase of cell‐free fetal DNA (cffDNA) in maternal circulation. Method Fifty pregnant women with singleton pregnancy were recruited prior to CVS. Maternal peripheral blood was collected before and after CVS. A methylation‐sensitive restriction enzyme digestion was used to select the placental‐derived hypermethylated promoter of the RASSF1A gene in maternal plasma, thus differentiating cffDNA from mother's cell‐free DNA (cfDNA), where the RASSF1A gene is normally hypomethylated. Total cfDNA and cffDNA amounts were compared before and after CVS in each patient. Data were compared using the Student t‐test. Results No significant difference before and after CVS was found between the following: (i) total cfDNA concentration in plasma (p = 0.695); (ii) cffDNA concentration in plasma (p = 0.612); and (iii) percentage of fetal DNA in plasma (p = 0.835). After dividing the cases on the basis of the sex of the fetus, maternal age, gestational age, number of pregnancies, position of the placenta, and presence of trisomy of the fetus, no difference in fetal and total DNA concentrations before and after CVS was observed. Conclusion The CVS does not seem to significantly disrupt the maternal–placental interface, as no significant increase of cffDNA in maternal plasma following CVS was observed. © 2013 John Wiley & Sons, Ltd.